Effect of method of learning and the ability to think of critical of learning outcomes IPA (Experiment Student Class V SDN Limbangan Central III District of Bl Limbangan Garut 2017) - Septie Elpridha,; Yetti Supriati,; Riana Bagaskorowati, (Technium Social Sciences Journal, 2020)
This study aims to know Influence Learning Method (Group Investigation and Guided Inquiry) and the ability to think critical of the results ipa learning. The research was conducted on students at Central Elementary School III Kecamtan Limbangan BI Limbangan Garut, with research subjects are students of class V. This study is an experimental method with 2 x 2 (factorial design). In this study, there are three variables that were examined are: Learning Outcomes IPA as the dependent variable (Y). While the independent variables are (1) Method of learning (Group Investigation and Guided Inquiry) (2) Critical Thinking Skills (high Critical thinking skills and critical thinking skills high). In this study, Yang became the target population (target) is all students of State Elementary School Middle Limbangan III Kecamtan BI Limbangan Garut. While the population is affordable is the class V SDN Middle Limbangan III Garut. The number of samples in this study are numbered students. Sampling using simple random sampling.Hasil showed that: (1). Learning outcomes IPA students that using model Group Investigation more high of Learning Outcomes Science students use learning methods Guided Inquiry, (2) There is an interaction effect between the use of teaching methods and ability Berpkiri Critical to the ability of learning outcomes IPA. (3) Students who have the ability Critical thinking high value IPA higher learning results when using the learning Group Investigation. (4) Students with Low Critical thinking skills, value learning outcomes IPA lower when using Guided Inquiry Learning.